STUDI TENTANG PERANAN GURU PPKn DI KECAMATAN PANGKALAN LESUNG DALAM MENINGKATKAN KARAKTER PEDULI SOSIAL - Ega Novia Putri; Ahmad Eddison; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The role of PPKn teachers is very important besides teaching knowledge, PPKn teachers also play a large role in shaping the character of students, so that students get a deep understanding and appreciation of values.Things that need to be considered as a teacher must be able to instill and have a social care character so that attitudes and actions to help others. This research aims as follows: To find out how the role of PPKn teachers in improving the character of social care for students in the sub-district Pangkalan Lesung. To find out how the social care character of students in the Pangkalan Lesung sub-district. To find out how the influence of the role of PPKn teachers in Pangkalan Lesung sub-district in improving the character of social care. The subject of this research was all students in Pangkalan Lesung Subdistrict which consisted of 4 schools with a total of 854 students. The sample in this study was taken based on a random sampling technique with 10% of the subjects from 854 students.Data collected through observation, questionnaires, interviews, and documentation. In analyzing data using quantitative descriptive techniques using statistical tests.The results showed that the role of the PPKn teacher in improving the character of social care was at very good levels. There is a significant influence on the role of PPKn teachers in improving the character of social care in sub-district Pangkalan Lesung, this is evidenced by the results of a simple linear regression test between variable X and variable Y, obtained Fcount (4,800) and the value of F table (3.96) shows that F_count > from F_table, so Ho is rejected and Ha is accepted so that hypothesis testing is accepted. Pengaruhnya rendah karena 23,4%.Key Words: Role, PPKn Teachers, Social Care Character